POSSIBLE CONSEQUENCES OF DECLARING CIVIL AND CUSTOMARY MARRIAGES VOID - Allen West; JC Bekker (Obiter, 2021)
The consequences of declaring a civil marriage entered into during the existence of a customary marriage or vice versa void could have nowhere been fully canvassed. On the face of it, it merely calls for a declaration of invalidity of the existing marriage, but it raises various ancillary issues which have not been addressed. We do not discuss the judgments declaring marriages void, but focus on the consequences of such judgments. For a variety of reasons it is important to determine whether a civil marriage, concluded subsequent to a customary marriage, is valid or ab initio void, or vice versa. To mention but one reason: “Where immovable property, a real right in immovable property, a bond or a notarial bond – (d) is registered in the name of a person who on the date of the registration was a party to a marriage governed by the Recognition of Customary Marriages Act, 1998 (Act 120 of 1998) the registrar shall on the written application by the person concerned and on the submission of the deed in question and of proof of the relevant facts, endorse the change in status or make a note of the effect that the said person is a party to a marriage in community of property, as the case may be” (S 17(4) of the Deeds Registries Act 47 of 1937). When a marriage is void, no consequences flow from it, except in so far as it may be deemed to be a putative marriage. Lawyers, officials and the public at large still do not seem to realize that in terms of sections 2(1) and (2) of the Recognition of Customary Marriage Act (120 of 1998) customary marriages entered into before and after commencement of the Act are for all purposes recognized as marriages. The case of Netshituka v Netshituka (426/10 [2011] ZACSA 120 dated 2011-07-20) has now given clear direction as to the validity or non-validity of civil marriages concluded after the Marriage and Matrimonial Property Law Amendment Act 3 of 1988. Also in Thembisile v Thembisile (2002 (2) SA 209 (T) par 32) Bertelsmann J held that a civil marriage contracted while the man was a partner in an existing customary marriage with another woman was void. The position of the validity of civil marriages, entered into prior to and after the said Amendment Act, will now be discussed.